Precipitation of Calcium Phosphates in the Presence of Collagen Type I on Four Different Bioactive Titanium Surfaces: an in Vitro Study - Victoria F. Stenport; Julia Olander; Per Kjellin; Fredrik Currie; Young-Taeg Sul; Anna Arvidsson (eJournal of Oral Maxillofacial Research, 2015)
Objectives: To compare the properties of calcium phosphate precipitation on four different bioactive surface preparations and one control surface in the simulated body fluid model with added collagen type I.